Gross Total Resection of Glioma with the Intraoperative Fluorescence-guidance of Fluorescein Sodium - Bo Chen, Haifeng Wang, Pengfei Ge, Jingwei Zhao, Wenchen Li, Huizi Gu, Guangming Wang, Yinan Luo, Dawei Chen (International Journal of Medical Sciences, 2012)
Objective. High dose fluorescein sodium has been utilized for fluorescence-guided tumor resection with conflicting reports on the efficacy of this procedure. The aim of this study was to reevaluate the utility and clinical limitations of using fluorescein sodium for the treatment and resection of glioma brain tumors. Methods. Patients diagnosed with glioma were divided into two groups with a total of 22 patients enrolled in the study: 1) the study group (n=10), patients that received intravenous injection of fluorescein sodium and 2) the control group (n=12), patients that did not receive injections during surgical resection. Quality of life was evaluated according to Karnofsky Performance Scale (KPS) score and neurological status. Fluorescein sodium was intravenously injected at a dose of 15-20mg/kg of body weight. Glioma resection was evaluated preoperative and postoperatively with enhanced Magnetic Resonance Imaging (MRI). Results. Significant differences in the gross total resection (GTR) rates were observed between the two patient groups (Fisher's Exact Test p=0.047). Progressive free survival was significantly longer in the study group (Student's T-Test p=0.033) as well as in the GTR group (Student's T-Test p=0.0001) compared to the control and non-GTR groups, respectively. Three patients in the study group and four patients in the control group had transient neurological deterioration. One patient in the control group had permanent hemiplegia. Conclusion. The intraoperative utility of using fluorescein sodium can significantly increase the GTR rate without obvious deterioration. In addition, we find that it is better to apply the fluorescein sodium in the cases with BBB (blood-brain barrier) disruption, which had been enhanced in preoperative MRI.